Interaksi referen dan konteks dalam antologi memoar Guru Welas Asih - Anjas Rusdiyanto Soleh; Atiqa Sabardila; Markhamah Markhamah (Universitas Mulawarman, 2023)
This study aims to describe the form of reference and context contained in the anthology of “Guru Welas Asih” memoirs. Qualitative descriptive method used in this study. This research aims at mapping references contained in the form of changes in the meaning of synesthesia. The data in this study are the form of words or phrases in the anthology of “Guru Welas Asih” memoirs. The data source for this research is an anthology of memoirs by the Komunitas Menulis Memoar entitled “Guru Welas Asih”. The memoir consists of 17 titles written by 17 members of the community. Provision of data in this study using note-taking techniques and documentation. Furthermore, data analysis uses the equivalent method with the application of referential techniques. The results of this study indicate that referent references cannot be separated from context. According to the findings of this study, the references contained in the anthology of “Guru Welas Asih” memoirs are: (1) reference words and (2) deictic words. The identified deixis is (1) persona deixis, (2) pointer deixis, and (3) place deixis. The type of reference refers to something that is bound by context. Therefore, the referent and context interact to show the reference.